Students’ Predominant Learning Style in EFL Writing Class - Faiz Hisyam Akbar; Peptia Asrining Tyas (EDUCAFL : Journal of Education of English as Foreign Language, 2022)
Many studies had examined writing strategies in ESL context. However, very few studies examined writing strategies by university students within foreign language learning contexts in Indonesia. Considering that reason, the researcher conducts a survey in EFL context focusing on writing strategies mostly used by 126 students enrolled in essay writing class. This study was conducted by using quantitative method, survey design, and English Writing Strategies Inventory (EWSI) questionnaire as the instruments. The result of this study shows that the predominant learning style of the students are determining the purpose and reading some materials related to the topic before start to write, checking the logical flow through paragraph when writing, and reviewing the writing to look for and correct grammatical errors after writing. It also found that the tendency of students to use EWSI is categorized as high since the frequency of strategy use in each category is high.